Novel energy management method for suppressing fuel cell degradation in hydrogen and electric hybrid energy storage systems compensating renewable energy fluctuations. (5th April 2018) - Zhang, Z.; Miyajima, R.; Inada, T.; Miyagi, D.; Tsuda, M.
Abstract: This research investigates an energy management method utilized in a hydrogen and electric hybrid energy storage system (HESS), which is utilized as an ancillary system for renewable energy electricity generation. To suppress the performance degradation of the fuel cell (FC), the newly proposed energy management method deals with main FC degradation causes, such as low humidification and frequent and rapid voltage changes. The entire HESS's performance is demonstrated using the proposed energy management method. In addition, a simulation is conducted to evaluate the proposed energy management method's performance in terms of both suppressing the FC's degradation and ensuring system efficiency. The results of the experiment and simulation show that the proposed energy management method can suppress the FC's harmful working states while maintaining high system efficiency. Highlights: Proposed an energy management method of H2 and electric hybrid energy storage system. The proposed method is effective on suppressing fuel cell's degradation. The proposed method is also remarkable on maintaining high system efficiency.